Evaluation of effective storage conditions and in-vitro bioaccessibility of vitamin A from native and modified sodium caseinate -vitamin A complexes. (August 2019) - Gupta, Chitra; Arora, Sumit; Sharma, Apurva; Sharma, Vivek
Abstract: Native sodium caseinate-Vitamin A (Vit A) complex Sodium caseinate-Vit A complex (NaCas-VA), and modified sodium caseinate-Vitamin A complexes succinylated sodium caseinate-Vit A complex (SNaCas-VA), reassembled sodium caseinate-Vit A complex (RNaCas-VA) and reassembled succinylated sodium caseinate-Vit A complex (RSNaCas-VA) were prepared and evaluated for effective storage conditions and in-vitro bioaccessibility of vitamin A. Complexes showed higher vitamin A stability when packed in aluminium laminate pouches as compared to microcentrifuge tubes. Free vitamin A (fat soluble) showed the lowest vitamin A stability followed by NaCas-VA, SNaCas-VA, RNaCas-VA and RSNaCas-VA complexes at different storage temperatures i.e. −20 °C, 4 °C and 37 °C. All complexes and free vitamin A (fat soluble) showed the lowest stability at 37 °C followed by 4 °C and −20 °C. Stability of milk protein -Vit A complexes were ascertained at two different pH (5.0 and 7.0). In-vitro bioaccessibility of vitamin A was higher for milk protein-Vit A complexes as compared to free vitamin A (fat soluble). Highlights: Aluminium laminate pouches proved an effective packaging material. Complexes showed the lowest stability at 37 °C and the highest at −20 °C. Free vitamin A (fat soluble) showed the lowest concentration. Bioavailability of vitamin A was higher for complexes as compared to free vitamin A.